The Influence of Digital Lifestyle and Personal Branding on Social Media on Students' Career Decisions - Yori Nur Maysha; Aina Tasya; Ammara Fazilatun Nisa; Syarifah Silvi Helmina Aryani; Hutomo Atman Maulana (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Purpose –This study aims to analyze the influence of digital lifestyle and personal branding on social media on students' career decisions, and to examine the role of reviews as a factor influencing both variables. Method –This research uses a quantitative approach with Partial Least Square-Structural Equation Modeling (PLS-SEM) as the analysis technique. The sample consists of 100 students selected using purposive sampling. Results – The results show that digital lifestyle and personal branding on social media have a positive and significant influence on students’ career decisions. In addition, reviews also have a positive and significant effect on both digital lifestyle and personal branding. These findings indicate that digital information and online reviews shape students’ behavioral patterns and self-image, which directly affect their career choices. Implications – This study highlights the importance of digital literacy and personal branding awareness in career development for university students.Originality – The originality of this research lies in the integration of the review variable as an initial predictor that links the influence of digital media to the career decision-making process in the digitalera.